On Bipolar Valued Fuzzy ð’Œ-Ideals in Hemirings - Mahmood, T.; Ejaz, A. (The Nucleus, 2015)
In this paper we discuss some results associated with Bipolar valued fuzzy ð‘˜ -ideals of hemirings. We also define bipolar valued fuzzy ð‘˜-intrinsic product and characterize ð‘˜- hemiregularhemirings by using their bipolar valued fuzzyð‘˜ -ideals.